A novel therapeutic strategy: remote dielectric sensing-guided management of pulmonary congestion. Issue 5 (May 2022) - Oshima, Akira; Imamura, Teruhiko; Onoda, Hiroshi; Hori, Masakazu; Kinugawa, Koichiro
Abstract: Management of pulmonary congestion is a key to improve mortality and morbidity in patients with congestive heart failure, but it is often challenging due to a lack of gold standard to accurately assess the lung fluid level. We had an 86-year-old man who was admitted to our institute due to worsening congestive heart failure. His pulmonary congestion was quantified repeatedly by the novel noninvasive device, remote dielectric sensing, and was optimally managed by the medication adjustment. Remote dielectric sensing might be a promising device to quantify pulmonary congestion and guide clinicians to optimize medications in addition to the conventional multi-modalities. <Learning objective: Remote dielectric sensing might be a promising device to quantify pulmonary congestion and guide clinicians to optimize medications in patients with congestive heart failure.>